Türkiye and Oman's Growing Relationship in the First Three Years of Sultan Haitham - Açıkel, Gökhan (Journal of History Culture and Art Research, 2023)
Sultan Qaboos bin Said ruled Oman from 1970 to 2020. After Sultan Qaboos died on January 10, 2020, Haitham bin Tarik began to rule the Sultanate of Oman on January 11, 2020. After taking over the administration, he attempted to rescue his country from its dire economic situation by instituting structural changes to make the country's administration more active and secure. He also adheres to Sultan Qaboos' management principles, particularly in foreign policy. The foundation and development of today's Turkish-Omani relations was largely accomplished during the reign of Sultan Qaboos bin Said. However, relations continue developing with the same goodwill and vision today. The reciprocal visits of President Recep Tayyip Erdogan and Sultan Haitham are one of the most anticipated developments in Turkish-Omani relations in this period. Türkiye’s collaborating with friendly and brotherly Oman in many fields and two countries’ sharing their experiences mutually will benefit both Türkiye and Oman, as well as the Gulf region in particular and the Middle East region in general. Türkiye can make significant contributions to Oman, particularly in the construction, tourism, health, and defense industries. The interest and affection of the people of Oman for Türkiye will be an important factor in establishing solid relations between the two countries. Oman is relatively unknown in Türkiye. As a result, Oman should work harder to increase its visibility in Türkiye. The fact that Oman is a beautiful tourist destination should be promoted more widely in Türkiye. Increasing the number of flights between the two countries is a positive step in this direction. With the two countries' cooperation, there is still a lot of work to do in the field of higher education. Both sides are working hard to further develop Turkish-Oman relations, and as a result, relations between the two countries will improve significantly in the future.